Serum Osteocalcin and Serum Osteopontin Levels in Osteoporotic Postmenopausal Women with and without Vertebral Fractures - Mohammed, Nawar S.; Turki, Kisma M.; Munshed, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Osteoporosis is a progressive systemic skeletal disorder characterized by low bone mass and micro-architectural deterioration of bone tissue spatially in postmenopausal women and its major complication fractures. Objective: The aim of this study was to find out the significance of serum OC and serum OPN levels with the incidence of osteoporosis and its major complication (fractures). Patients and Methods: Eighty-five postmenopausal women (PMW) whose ages were fifty years and over categorized into three groups: osteoporosis PMW without VFs (n=30), osteoporosis PMW with VFs (n=28), and healthy PMW (n=27). Sera samples were analyzed for alkaline phosphatase, calcium and phosphorous by using spectrophotometric kit. Serum OC and serum OPN levels were measured by ELISA kits. Results: Bone Mineral Density (BMD) and T-score were significantly lower in osteoporotic PMW with and without VFs as compared with healthy PMW (p=0.0001, p=0.0001, respectively). Serum OC levels and serum OPN levels were elevated significantly in osteoporotic PMW with and without VFs as compared with healthy PMW (p=0.0001, p=0.0001, respectively), the levels of serum OC and OPN showed a significant positive correlation with age in osteoporotic PMW. There is a significant positive correlation between serum OC levels and serum OPN levels in osteoporotic PMW and non-significant correlation was found in healthy PMW. Conclusion: The levels of serum OC and OPN can be used as a biochemical indicator in the diagnosis of postmenopausal osteoporotic women